Evaluation of the acute toxic effect of azoxystrobin on non-target crayfish (Astacus leptodactylusEschscholtz, 1823) by using oxidative stress enzymes, ATPases and cholinesterase as biomarkers - Uckun, Aysel Alkan; Oz, Ozden Barim (Taylor & Francis Ltd, 2021)
Azoxystrobin is a broad-spectrum fungicide used worldwide. Since azoxystrobin spreads to large areas, its toxic effects on non-target organisms have aroused interest. In this study, the acute toxicity (96 h) of azoxystrobin on the crayfish (Astacus leptodactylus)was examined by using various biomarkers. The 96 h-LC(50)dose (1656 mg L-) and its three sub-doses (828, 414, 207 mg L-1) were applied to crayfish. Superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities were increased significantly compared to the control in hepatopancreas, gill and muscle tissues. The activities of acetylcholinesterase (AChE) and glutathione S-transferase (GST) increased, and glutathione reductase (GR) activity decreased significantly in hepatopancreas. Level of reduced glutathione (GSH) decreased significantly. The content of malondialdehyde (MDA) increased in a dose-dependent manner in all azoxystrobin treatments with the exception of the lowest dose (207 mg L-1)treatment. ATPases (Na+/K+-ATPase, Mg2+-ATPase, Ca2+-ATPase, total ATPase) were significantly inhibited in gill and muscle tissues. The results of the present study indicate that azoxystrobin induces oxidative stress, and has adverse effects on activities of AChE and ATPases in crayfish.
Keywords: Fungicide; toxicity; crustacean; bioindicator; biochemical markers